The Carcinoma–Stromal Ratio of Colon Carcinoma Is an Independent Factor for Survival Compared to Lymph Node Status and Tumor Stage - Wilma E. Mesker; Jan M. C. Junggeburt; Karoly Szuhai; Pieter de Heer; Hans Morreau; Hans J. Tanke; Rob A. E. M. Tollenaar (Cellular Oncology)
Background: Tumor staging insufficiently discriminates between colon cancer patients with poor and better prognosis. We have evaluated, for the primary tumor, if the carcinoma-percentage (CP), as a derivative from the carcinoma-stromal ratio, can be applied as a candidate marker to identify patients for adjuvant therapy. Methods: In a retrospective study of 63 patients with colon cancer (stage I–III, 1990–2001) the carcinoma-percentage of the primary tumor was estimated on routine H&E stained histological sections. Additionally these findings were validated in a second independent study of 59 patients (stage I–III, 1980–1992). (None of the patients had received preoperative chemo- or radiation therapy nor adjuvant chemotherapy.) Results: Of 122 analyzed patients 33 (27.0%) had a low CP and 89 (73.0%) a high CP. The analysis of mean survival revealed: overall-survival (OS) 2.13 years, disease-free- survival (DFS) 1.51 years for CP-low and OS 7.36 years, DFS 6.89 years for CP-high. Five-year survival rates for CP-low versus CP-high were respectively for OS: 15.2% and 73.0% and for DFS: 12.1% and 67.4%. High levels of significance were found (OS p < 0.0001, DFS p < 0.0001) with hazard ratio’s of 3.73 and 4.18. In a multivariate Cox regression analysis, CP remained an independent variable when adjusted for either stage or for tumor status and lymph-node status (OSp < 0.001, OSp < 0.001). Conclusions: The carcinoma-percentage in primary colon cancer is a factor to discriminate between patients with a poor and a better outcome of disease. This parameter is already available upon routine histological investigation and can, in addition to the TNM classification, be a candidate marker to further stratify into more individual risk groups.